2020
DOI: 10.3390/ijms21030706
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Transcription Factor MYB14 on Defense Mechanisms in Vitis quinquangularis-Pingyi

Abstract: In the current study, we identified a transcription factor, MYB14, from Chinese wild grape, Vitis quinquangularis-Pingyi (V. quinquangularis-PY), which could enhance the main stilbene contents and expression of stilbene biosynthesis genes (StSy/RS) by overexpression of VqMYB14. The promoter of VqMYB14 (pVqMYB14) was shown to be induced as part of both basal immunity (also called pathogen-associated molecular pattern (PAMP)-triggered immunity, PTI) and effector-triggered immunity (ETI), triggered by the elicito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…In the Rpv12-mediated response, we vice versa found statistically significant induction of a thaumatin-like protein gene similar to a V. amurensis ortholog that impaired mycelial growth, causing hyphal malformation, in transgenic lines of sensitive controls 70 . An increasing number of yet genetically uncharacterized sources of P. viticola resistance have emerged in the past years from Asian species, which include V. pseudoreticulata 71 and Vitis quinquangularis 72 . Further studies will be needed to clarify if these novel downy mildew resistances share the same type of ETI and follow the same lines of defence reactions as those observed in Rpv12-mediated resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In the Rpv12-mediated response, we vice versa found statistically significant induction of a thaumatin-like protein gene similar to a V. amurensis ortholog that impaired mycelial growth, causing hyphal malformation, in transgenic lines of sensitive controls 70 . An increasing number of yet genetically uncharacterized sources of P. viticola resistance have emerged in the past years from Asian species, which include V. pseudoreticulata 71 and Vitis quinquangularis 72 . Further studies will be needed to clarify if these novel downy mildew resistances share the same type of ETI and follow the same lines of defence reactions as those observed in Rpv12-mediated resistance.…”
Section: Discussionmentioning
confidence: 99%
“…224,225 Subsequent studies based on the use of Ca 2+ ionophores or channel blockers supported these evidences, demonstrating that increase in the cytosolic Ca 2+ concentration is fundamental for the MeJA-and cyclodextrin-mediated induction of stilbene biosynthesis. [226][227][228][229] Recently, Luo et al 230 showed that treatment with a Ca 2+ ionophore induces the expression of a transcription factor (TF) involved in the regulation of STS in V. quinquangularis-Pingyi and can be associated to early signaling events in the salicylic acid (SA)-mediated flg2-triggered plant immunity. Kiselev et al 228 showed that, together with STS genes, treatment of grapevine cell cultures with Ca 2+ channel blockers and a Ca 2+ ionophore also affected the mRNA levels of calcium-dependent protein kinase (CDPK) genes.…”
Section: Regulation By Calcium Signalingmentioning
confidence: 99%
“…Among the 11 articles in the Special Issue on plant genes conferring resistance to biotic stresses [3,[25][26][27][28][29][30][31][32][33][34], seven articles reported results from single resistant genes (or QTL) for crops and plant species, including soybean, rice, wheat, Dasypyrum villosum, Aegilops searsii, Capsicum annuum, and Vitis quinquangularis. The other four articles [27,29,30,32] analyzed multiple QTLs or genomic regions for one or more diseases.…”
Section: Chromosomal Distribution Patterns Of Genes For Abiotic-stresmentioning
confidence: 99%
“…Plants need to possess genes conferring tolerance to these abiotic stresses to adapt to the changing environment, due to global climate changes, in which they are growing. Due to the coevolution of plants and stress-causing organisms [3], plants need to possess multiple resistance genes to deal with the rise of new virulence in stress-causing organisms. Plant breeders are constantly looking for new resistance genes to combat evolving organisms that pose a threat to susceptible crops.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation